Pengembangan Media Komik dalam Pembelajaran Menulis Teks Anekdot untuk Meningkatkan Pemahaman Siswa Kelas X SMA Swasta Al-Hidayah Medan - Sonia, Sofie; Deliani, Deliani; Rita, Rita (Medan Resource Center, 2023)
The purpose of this research was to develop and assess the feasibility of comic media for teaching anecdote writing to Class X students at SMAS Al-Hidayah Medan. Following the Research and Development approach by Borg and Gall, this study involved seven steps: research and data collection, planning, product draft development, preliminary field testing, revising trial results, main field testing, and improving the operational product. The sample comprised 24 students from a population of 46. The assessment results indicated that the developed product was deemed feasible. Material experts I and II rated it as